RESPONSIBLE EMPLOYMENT POLICY: COMPARATIVE ANALYSIS OF CROATIAN, SWEDISH AND DANISH ACTIVE LABOUR MARKET POLICIES - Spadina, Helga (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Reduction of unemployment has been one of the crucial areas of social policies for past decades because it is a key to economic growth and development. Taking into consideration fast changing labour market needs and rapid transformation of labour relations, European public employment services are continuously creating new measures of active employment with the aim to assist as many unemployed beneficiaries as possible and to swiftly re-integrate them into the labour markets. The main goal of active labour market programs is to make the matching process more efficient and to increase the number of successful matches of job vacancies and job seekers.By are using examples of selected active employment measures in Croatia, Sweden and Denmark, we are providing comparative analysis of active labour market measures. The paper is divided into five sections. Section 1 provides overview of measures to reduce unemployment; in section 2 we outline the purpose of active labour market measures; section 3 provides comparative analysis of five of the Croatian, Danish and Swedish active labour market programs and we close with description of new activation strategies during Covid – 19 in Croatia.The conclusion of the paper is that only by doing comprehensive analysis of impact of active labour market measures from the perspective of newly acquired employability and the increase in acquisition of new skills, along with analysis of level of social inclusion of jobseekers, we can engage in creation of impactful social policies for employment.Keywords: active labour market policies, activation strategies, unemployment, social policy, Covid.
Keywords: active labour market policies; activation strategies; unemployment; social policy; Covid-19